Impact of Physician Gender Selection on Patient's Perceptions of Experience With Women's Health [9K]. (May 2018) - Turrentine, Mark; Ramirez, Mildred; Stark, L. M.; Snead, Carrie; Schulkin, Jay
Abstract : INTRODUCTION: To evaluate women's attitudes about the role of obstetrician-gynecologists (ob-gyn) gender selection and their perceptions of knowledge, experience, and understanding with women's health. METHODS: Two large private practice ob-gyn groups anonymously surveyed patients at scheduled office visits to explore the role of gender in the selection of their ob-gyn and their perceptions of the physician's knowledge, experience, and understanding with women's health. The Mann-Whitney U test was utilized for comparisons. RESULTS: In 2017, 996 patients were surveyed with 803 returned (81% response rate). Women who saw a female physician were more likely to be younger (36 versus 39 years) and married (88% versus 82%) than women seen by a male. Women who saw female ob-gyns (compared to those that saw a male) reported that the gender of their physician was important to them (62% versus 20%, P <.01). Women who saw a female ob-gyn perceived their physicians have a greater knowledge (27% versus 3%, P <.01), experience (51% versus 14%, P <.01), and understanding (54% versus 8%, P <.01) with women's health in comparison to women who choose a male. The top three rank-order reasons women choose a female ob-gyn were physician ratings, gender, and office location. In contrast, the reason women choose a male ob-gyn were physician ratings, availability, and office location. CONCLUSION: Women who seek a female ob-gyn feel strongly about the gender and have perceptions their physicians are more knowledgeable, experienced, and understanding about women's health compared to a male ob-gyn.